Performance Evaluation of the Quantamatrix QMAC-dRAST System for Rapid Antibiotic Susceptibility Testing Directly from Blood Cultures - Rosselin, Manon; Prod’hom, Guy; Greub, Gilbert; Croxatto, Antony (Microorganisms (Basel), 2022)
Objectives: Rapid antibiotic susceptibility testing (AST) for positive blood cultures can improve patient clinical outcomes if the time to an effective antimicrobial therapy is shortened. In this study, we tested the Quantamatrix dRAST system (QMAC-dRAST), a rapid AST system based on time-lapse microscopic imagery of bacterial colony formation in agarose. Methods: Evaluation of the QMAC-dRAST was performed from 250 monobacterial blood cultures including 130 Enterobacterales, 20 non-fermentative Gram-negative bacteria, 69 staphylococci and 31 enterococci. Blood cultures were recovered from anonymous patients or from spiking experiments to enrich our study with bacterial species and resistant strains. Categorical agreement (CA), minor errors (me), major errors (ME) and very major errors (VME) were calculated in comparison to the results obtained from the BD Phoenix™ M50. Discrepancies between the Phoenix™ M50 and QMAC-dRAST results were investigated using the gradient strip method. The repeatability and reproducibility performance of the QMAC-dRAST was assessed for 16 strains, each strain being tested five times from a spiked blood culture. Results: The overall CAs for Enterobacterales, non-fermentative Gram-negative bacteria, staphylococci and enterococci were 95.1%, 91.2%, 93.4% and 94.5%, respectively. The VME percentage was below 4% for all the groups except for staphylococci, which showed a VME rate of 7%. The median time to result was 6.7 h (range: 4.7–7.9). Repeatability and reproducibility assays showed a high reliability of AST results with best and worst ratios of 98.8% and 99.6% and 95.0% and 98.3%, respectively. Conclusions: The QMAC-dRAST is a fast and reliable system to determine AST directly from monobacterial blood cultures with a major TAT reduction compared to conventional AST testing.